Simultaneous total hip and knee arthroplasties in hemophilic arthropathy: series of 5 cases - Özgür Mert Bakan; Arman Vahabi; Elcil Kaya Biçer; Fahri Şahin; Kaan Kavaklı (Acta Orthopaedica et Traumatologica Turcica)
Objective: This study aimed to compare preoperative and postoperative measures in haemophiliacs who had simultaneous total hip and knee arthroplasties.